Pengaruh Earning Per Share Dan Price Earning Ratio Terhadap Return Saham Pada PT Bank Jago Tbk Tahun 2014-2023 - Sam De Fernandesz, Agknia; Rachmawaty Rachmawaty (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to analyze the effect of Earning Per Share (EPS) and Price Earning Ratio (PER) on stock returns at PT Bank Jago Tbk for the period 2014–2023. The background of this research is based on significant fluctuations in the company’s stock price, reflecting the dynamics of financial performance and investor expectations. The method used is a quantitative approach with multiple linear regression analysis. The data used are secondary data from the company’s annual financial statements. The partial test results (t-test) show that EPS has a t-value of 1.708 and a t-table value of 1.894 (1.708 < 1.894), with a significance value of 0.131 (> 0.05), indicating that EPS has no significant effect on stock returns. Meanwhile, PER has a t-value of 3.520 and a t-table value of 1.894 (3.520 > 1.894), with a significance value of 0.010 (< 0.05), indicating that PER has a significant effect on stock returns. However, the simultaneous test (F-test) shows an F-value of 6.248 > F-table value of 4.73, with a significance of 0.028 (< 0.05), indicating that both EPS and PER simultaneously influence stock returns. The coefficient of determination (R²) is 0.641, which means that EPS and PER account for 64.1% of the variation in stock returns Keywords: Earning Per Share, Price Earning Ratio, Stock Return, PT Bank Jago Tbk